2018
DOI: 10.3390/app8091493
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Interface-State Distributions in Polymer-Based Metal-Insulator-Semiconductor Capacitors by Impedance Spectroscopy

Abstract: Information on localized states at the interfaces of solution-processed organic semiconductors and polymer gate insulators is critical to the development of printable organic field-effect transistors (OFETs) with good electrical performance. This paper reports on the use of impedance spectroscopy to determine the energy distribution of the density of interface states in organic metal-insulator-semiconductor (MIS) capacitors based on poly(3-hexylthiophene) (P3HT) with three different polymer gate insulators, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The (D M + D H ) monotonically decreases on average with an increase in qΨ S . The values of (D M + D H ) are comparable to those of MOS capacitors having crystal Si [35], amorphous Si [36], SiC [56], GaN [57], and polymers [58,59] as a semiconductor. When integrating (D M + D H ) with respect to qΨ S , the area densities are obtained as 4.9, 6.2, and 9.7 × 10 11 cm −2 for t P = 10, 20, and 30 s, respectively.…”
Section: Mos Capacitor Characteristicsmentioning
confidence: 58%
“…The (D M + D H ) monotonically decreases on average with an increase in qΨ S . The values of (D M + D H ) are comparable to those of MOS capacitors having crystal Si [35], amorphous Si [36], SiC [56], GaN [57], and polymers [58,59] as a semiconductor. When integrating (D M + D H ) with respect to qΨ S , the area densities are obtained as 4.9, 6.2, and 9.7 × 10 11 cm −2 for t P = 10, 20, and 30 s, respectively.…”
Section: Mos Capacitor Characteristicsmentioning
confidence: 58%
“…For further in-depth analysis on the dielectric/organic semiconductor interfaces, we assessed the interface trap density (D it ) by a conductance method, which has been used widely for the trap density analysis in Si-based electronics. [65] As the equivalent circuit models of organic metal-insulator-semiconductor (MIS) capacitors are similar to those of Si-based metal-oxide semiconductor (MOS) capacitors, [66,67] D it analysis via a conductance method has been utilized broadly for the organic devices as well. [53,[68][69][70] We monitored the D it variation according to the frequency in the subthreshold region (V G from −1 to −2 V) by using the MIS stack (Figure S5, Supporting Information) and the maximum D it (D it,max ) value was extracted for each V G (Figure 2h).…”
Section: Fabrication Of Otfts Using the Hybrid Dielectric Layersmentioning
confidence: 99%
“…12, pp: 3235-3241 2323 It was observed that the decomposition temperature (T 5 , T 10 and T g ) of the PI was increased by about 38, 35 and 40 ο C, respectively, when the thickness of PI film was increased. This behavior is due to the increase of the number of imide bonds and the decrease of average distance between imide groups which enhances the intermolecular interaction [14,15].…”
Section: Rasheed and Kareemmentioning
confidence: 99%